POTENSI PANTAI PERANCAK SEBAGAI DAYA TARIK WISATA DESA TIBUBENENG KUTA UTARA BADUNG - Murvianti, Swandita Dyah; Arida, I Nyoman Sukma (JURNAL DESTINASI PARIWISATA; Vol 3 No 2 (2015): VOL 3, NO 2 (2015): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2015.v03.i02.p09, 2015)
ABSTRACT This research discusses the potential Perancak beach as tourist attraction located at Tibubeneng village, sub-dictrict north of Kuta regency of badung. Perancak beach offers a wide range of potential such as beach waves for surfing, white and brown sand, coastal area, sunset in the afternoon, estuaries are used for swimming and Perancak temples used for religious tourism. With a wide range of potential, yet there are those who manage the beach so that the potential of the less well-known by domestic and foreign travelers. Method used is descriptive qualitative method. Based on the result of the research, there is a picture of the potential physical and non-physical potential as well as all aspects of supporting the exixtence of Tibubeneng village tourism. After observed regarding the potential for the continued used of the theory by analyzing the SWOT : Strength, Weakness, Opportunity and Threats. Of the result of the analysis, it has the potential Perancak beach that can be enjoyed by domestic tourists and foreign tourist but in the absence of the conditions at the beach manajer Perancak not maintained. Thus need special managers so that the potential contained in Perancak beach can be put to good use and can giving provide benefits for economies of Tibubeneng village.
Keywords: potential, tourist attraction